Standard handbook of biomedical engineering and design - Kutz, Myer
Includes bibliographical references and index.; Biomedical systems analysis -- Mechanics of the human body -- Biomaterials -- Bioelectricty -- Design of medical devices and diagnostic instrumentation -- Engineering aspects of surgery -- Rehabilitation engineering -- Clinical engineering.; Publisher's description: The dynamic field of biomedical engineering has not only changed the way we live, but has even inspired the creation of more than one popular TV series (The Bionic Man) and a number of sci-fi movies. And it has touched us in other ways as well--it made a household name of artificial heart recipient Barney Clark. The Standard Handbook of Biomedical Engineering bridges the gap between engineering principles and biological systems. Over 40 experts from universities and medical centers throughout North America and Israel have produced a practical reference for the biomedical professional who is seeking to solve a wide range of engineering and design problems, whether to enhance a diagnostic or therapeutic technique, reduce the cost of manufacturing a medical instrument or prosthetic device, improve the daily life of a patient with a disability, or increase the effectiveness of a hospital department. Coverage includes not only fundamental principles but also numerous recent advances in this fast moving discipline. The Handbook offers a breadth and depth of biomedical engineering coverage unmatched in any other reference.; Mode of access: Internet.